Biological impact of α genes, β haplotypes, and G6PD activity in sickle cell anemia at baseline and with hydroxyurea - Bernaudin, Françoise; Arnaud, Cécile; Kamdem, Annie; Hau, Isabelle; Lelong, Françoise; Epaud, Ralph; Pondarré, Corinne; Pissard, Serge (Blood advances, 2018)
Sickle cell anemia (SCA), albeit monogenic, has heterogeneous phenotypic expression, mainly related to the level of hemoglobin F (HbF). No large cohort studies have ever compared biological parameters in patients with major β-globin haplotypes; ie, Senegal (SEN), Benin (BEN), and Bantu/Central African Republic (CAR). The aim of this study was to evaluate the biological impact of α genes, β haplotypes, and glucose-6-phosphate dehydrogenase (G6PD) activity at baseline and with hydroxyurea (HU). Homozygous HbS patients from the Créteil pediatric cohort with available α-gene and β-haplotype data were included (n = 580; 301 females and 279 males) in this retrospective study. Homozygous β-haplotype patients represented 74% of cases (37.4% CAR/CAR, 24.3% BEN/BEN, and 12.1% SEN/SEN). HU was given to 168 cohort SCA children. Hematological parameters were recorded when HbF was maximal, and changes (ΔHU-T0) were calculated. At baseline, CAR-haplotype and α-gene numbers were independently and negatively correlated with Hb and positively correlated with lactate dehydrogenase. HbF was negatively correlated with CAR-haplotype numbers and positively with BEN- and SEN-haplotype numbers. The BCL11A/rs1427407 “T” allele, which is favorable for HbF expression, was positively correlated with BEN- and negatively correlated with CAR-haplotype numbers. With HU treatment, Δ and HbF values were positively correlated with the BEN-haplotype number. BEN/BEN patients had higher HbF and Hb levels than CAR/CAR and SEN/SEN patients. In conclusion, we show that BEN/BEN patients have the best response on HU and suggest that this could be related to the higher prevalence of the favorable BCL11A/rs1427407/T/allele for HbF expression in these patients. •α genes and CAR haplotypes independently impact hemolytic anemia severity; low G6PD-activity impacts anemia severity in CAR/CAR patients.•BEN/BEN patients have a higher prevalence of the favorable BCL11A/rs1427407 T allele and a better response to HU than CAR/CAR patients. [Display omitted]